Determination Of Formaldehyde In Tofu From Ciputat Traditional Market With Colorimetry Method - Zilhadia Zilhadia; Sanny Susanti (Syarif Hidayatullah State Islamic University, 2011)
Tofu, a food product made from soybean, contain water and it is very easy to overgrown microbes.Based on a survey, many products of tofu contain formaldehyde as preservative. Formaldehyde is apreservative that the use is prohibited for food because it can cause cancer in humans. The aim of thisstudy was determined concentration of formaldehyde in tofu from traditional market Ciputat usingSpectrophotometer UVI-VIS. Steam distillation was used for sample extraction process. Distillate wasreacted with Nash reagent. The equation of calibration curve is y=0,0032x – 0,0079 and correlationcoefficient of the linear regression of 0,9992. The experimental results obtained LOD value of11.1328 μg/ml, LOQ value of 37,1094 μg/mL The precision of this analytical method were lower than2% for each of the sample, while method’s accuration for tofu was 98,69% ± 0,4085%. Results ofsample analysis from Ciputat market, samples were detected containing formaldehyde. Formaldehydeconcentrations are 104,87 μg/mL, 11,21 μg/mL, 1,96 μg/mL, 190,80 μg/mL, 201,98 μg/mL, 10,47μg/mL, and 3,31 μg/mL.